NSUN2 Promotes Head and Neck Squamous Cell Carcinoma Progression by Targeting EMT-Related Gene LAMC2 in an m5C-YBX1-Dependent Manner - Shuojin Huang; Congyuan Cao; Dongxiao Tang; Yiwen Liu; Wanhang Zhou; Lianlian Liu; Xin Zheng; Qianting He; Anxun Wang (Biomedicines)
Background/Objectives: Head and neck squamous cell carcinoma (HNSCC) is a prevalent and aggressive cancer with high rates of metastasis and poor prognosis. Recent research highlights the role of 5-methylcytosine (m5C) in cancer progression. NSUN2, an m5C methyltransferase, has been implicated in various cancers, but its role in HNSCC remains elusive. Methods: NSUN2 expression and its impact on HNSCC were analyzed by using clinical samples and bioinformatic analysis. m5C-Bis-Seq was used to assess changes in mRNA m5C modification and identify downstream targets. Both in vitro and vivo studies were performed to evaluate the impact of NSUN2 manipulation on tumor growth and metastasis. Results: Results indicated that NSUN2 was significantly upregulated in HNSCC tissues compared to normal tissues and was associated with poor prognosis. NSUN2 knockdown led to decreased cell proliferation, migration, and invasion in vitro and reduced tumorigenicity and lymph node metastasis in vivo. m5C-Bis-Seq revealed altered m5C-modification patterns upon NSUN2 knockdown, with LAMC2 identified as a key downstream target. Conclusions: NSUN2-mediated m5C-modification enhanced LAMC2 stability, promoting epithelial–mesenchymal transition (EMT) signaling pathways. These findings demonstrate that NSUN2 promotes the initiation and progression of HNSCC by stabilizing the LAMC2 transcript through m5C-dependent mechanisms, offering a promising epitranscriptomic-targeted therapeutic approach for HNSCC.